Quizizz As a Game Based Interactive Learning Media in the Era of Independent Curriculum - Vera Astuti; Niken Purnamasari; Bintang Lazuardi Benteng Buana Muslim (Indonesian Journal Publisher, 2025)
The main objective of this research is to evaluate the use of Quizizz as a web-based learning tool to meet the demands of technological advancement in the Merdeka Curriculum era. This study employed a descriptive quantitative design with purposive sampling, involving 120 students. Data were collected using a Likert-scale questionnaire distributed through Google Forms, and analyzed using instrument validity checks by five experts with the Aiken V formula and reliability testing. The instrument was then used to measure student responses based on assessment indicators from I Nyoman Sudana Degeng. The results showed that the Quizizz application as a game-based learning medium was categorized as very good based on student responses in supporting the classroom learning process. In conclusion, Quizizz proves to be an effective digital tool aligned with the technological demands of the Independent Curriculum.